Control system design guide a practical guide - Ellis, George (George H.) (Amsterdam ; Boston : Elsevier Academic Press, 2004)
Control System Design Guide, 3E will help engineers to apply control theory to practical systems using their PC. This book provides an intuitive approach to controls, avoiding unnecessary mathematics and emphasizing key concepts with more than a dozen control system models. Whether readers are just starting to use controllers or have years of experience, this book will help them improve their machines and processes. * Teaches controls with an intuitive approach, avoiding unnecessary mathematics. * Key topics are demonstrated with realistic models of control systems. * All models written in Visual ModelQ, a full graphical simulation environment available freely via the internet. * New material on OBSERVERS explained using practical applications. * Explains how to model machines and processes, including how to measure working equipment; describes many nonlinear behaviours seen in industrial control systems. * Electronic motion control, including details of how motors and motor feedback devices work, causes and cures of mechanical resonance, and how position loops work.
Introduction to Controls; The Frequency Domain; Tuning a Control System; Delay in Digital Controllers; The z-Domain; Six Types of Controllers; Disturbance Response; Feed-Forward; Filters in Control Systems; Introduction to Observers in Control Systems; Introduction to Modeling; Nonlinear Behavior and Time Variation; Seven Steps to Developing a Model; Encoders and Resolvers; Basics of the Electric Servomotor and Drive; Compliance and Resonance; Position-Control Loops; Using the Luenberger Observer in Motion Control. Appendices: Active Analog Implementation of Controller Elements; European Symbols for Block Diagrams; The Runge-Kutta Method; Development of the Bilinear Transformation; The Parallel Form of Digital Algorithms; Basic Matrix Math.
Includes bibliographical references and index.
Keywords: Automatic control; System design; Electronic books